2010
DOI: 10.3109/10253890.2010.482628
|View full text |Cite
|
Sign up to set email alerts
|

Allopregnanolone and suppressed hypothalamo–pituitary–adrenal axis stress responses in late pregnancy in the rat

Abstract: In rats, late pregnancy is associated with suppressed hypothalamo-pituitary-adrenal (HPA) axis responses to a variety of stressful stimuli. The result is reduced corticosterone secretion following stress, which is considered to give some protection to the fetuses from adverse glucocorticoid programming and limits the catabolic effect of corticosterone, hence minimizing maternal energy expenditure. We have used a model of immune challenge in which systemic administration of the cytokine, interleukin-1β (IL-1β),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 69 publications
(73 reference statements)
1
34
0
1
Order By: Relevance
“…It has been suggested that this mechanism not only serves to promote appropriate metabolic adaptations necessary for a successful pregnancy outcome, but to also minimize fetal exposure to excessive levels of glucocorticoids in utero that may contribute to detrimental fetal programming (Herrera 2000). While several mechanisms have been proposed to explain the pregnancy-related adaptations in the brain that underpin HPA axis hypo-responsiveness during pregnancy, evidence from animal models suggests that ALLO may play a critical role in suppressed HPA axis responses to stress in pregnancy (Brunton et al 2009; Brunton and Russell, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this mechanism not only serves to promote appropriate metabolic adaptations necessary for a successful pregnancy outcome, but to also minimize fetal exposure to excessive levels of glucocorticoids in utero that may contribute to detrimental fetal programming (Herrera 2000). While several mechanisms have been proposed to explain the pregnancy-related adaptations in the brain that underpin HPA axis hypo-responsiveness during pregnancy, evidence from animal models suggests that ALLO may play a critical role in suppressed HPA axis responses to stress in pregnancy (Brunton et al 2009; Brunton and Russell, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of progesterone and its metabolite, allopregnanolone, in pregnancy ensure that there is an enhancement of the allopregnanolone-mediated inhibition of the noradrenergic input to the PVN from the nucleus of the solitary tract (Brunton et al 2005(Brunton et al , 2009Brunton and Russell 2010). Thus, pregnant females respond to stressors with less of an increase in GC than do nonpregnant females (Brunton et al 2005(Brunton et al , 2009Slattery and Neumann 2008).…”
Section: Stress Obesity and Neonatal Programmingmentioning
confidence: 92%
“…Adaptations during pregnancy ensure that the foetus is relatively protected against increases in glucocorticoids [183]. Elevated levels of progesterone and its metabolite, allopregnanolone, ensure that the allopregnanolone-mediated inhibition of the noradrenergic input to the PVN from the nucleus of the solitary tract is enhanced [199][200][201] so that pregnant females respond to stress with less of an increase in glucocorticoids than do nonpregnant females [199,200,202]. Also, placental 11 -hydroxysteroid dehydrogenase-2 , responsible for deactivating glucocorticoids before they can reach the foetus, plays a crucial role in ameliorating the impact of maternal glucocorticoids [203].…”
Section: Glucocorticoidsmentioning
confidence: 99%